Transient Permeability of a Deep‐Seated Subduction Interface Shear Zone - J. Muñoz‐Montecinos; W. M. Behr (Geophysical Research Letters, 2023)
Abstract Slow slip and tremor is observed along many subduction margins and is commonly linked to fluid pressure variations and migration. Accurate estimates of porosity and permeability around subduction megathrust shear zones are vital for understanding fluid‐seismicity interactions. We use high‐resolution digital outcrop data and (micro)structural analysis to assess transient permeability and porosity of a deep‐seated subduction interface exposed on Syros Island, Greece. We document the orientations, relative timing, and opening aperture (based on crack‐seal textures) of veins that were emplaced synkinematically with ductile deformation during early exhumation within the subduction channel. Our findings indicate high permeability through vein‐filled fractures amidst a lower permeability matrix, with transient, fracture‐controlled permeabilities ranging from 10−14 to 10−15 m2 and fracture porosities of 1%–10%. These estimates align with low‐end values from seismological/geodetic observations in active subduction zones, and are also consistent with fault‐valve‐like numerical models that suggest high background‐to‐transient permeability contrasts favor unstable slip.